If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2a + -1b) = 8(4a + -3b) (2a * 2 + -1b * 2) = 8(4a + -3b) (4a + -2b) = 8(4a + -3b) 4a + -2b = (4a * 8 + -3b * 8) 4a + -2b = (32a + -24b) Solving 4a + -2b = 32a + -24b Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-32a' to each side of the equation. 4a + -32a + -2b = 32a + -32a + -24b Combine like terms: 4a + -32a = -28a -28a + -2b = 32a + -32a + -24b Combine like terms: 32a + -32a = 0 -28a + -2b = 0 + -24b -28a + -2b = -24b Add '2b' to each side of the equation. -28a + -2b + 2b = -24b + 2b Combine like terms: -2b + 2b = 0 -28a + 0 = -24b + 2b -28a = -24b + 2b Combine like terms: -24b + 2b = -22b -28a = -22b Divide each side by '-28'. a = 0.7857142857b Simplifying a = 0.7857142857b
| 11=-4(4m-5)+2(m+5) | | 5*-17=-x+7 | | (7k-3)(k-2k+7)= | | 5(5p+6)+5(1-3p)=75 | | (21a+5)-(4a+13)=11 | | 8u-24= | | -14=-3(2+4n)+4(-2n-2) | | -31-7x=-2(x-2) | | -6(-a+4)=3a-30 | | p=223x | | 3(-n+2)-1=-3n+5 | | -32-7=-3(-8+7v) | | 2n+7=11 | | 2k-(k-1)=7 | | 1+5p= | | -4+5(k-2)=7k-8 | | 15x+187=3x | | -2a+14b=6c | | 8k-(4k-1)=28 | | -6x+6(5+x)=-8x-26 | | -r=6-8(r+6) | | -7-5(1-8x)=-212 | | Y/3-11=16 | | 5-x=3.5 | | -7(1+8n)=385 | | 2h-(h-1)=9 | | 5v+8=63 | | x(x^3-x^2-3x+1)+2=0 | | x^4-x^3-3x^2+x=0 | | x^4-x^3-3x^2+x+2=0 | | 150=-3(-8-6r) | | x^4-x^3-3x^2+x^1+2=0 |